2002
DOI: 10.1038/modpathol.3880541
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-Cell Lymphoma Mimicking Marginal Zone B-Cell Lymphoma

Abstract: Peripheral T-cell lymphoma (PTCL) may assume a variety of histologic and cytologic appearances. We describe eight cases of PTCL morphologically simulating marginal zone B-cell lymphoma. We reviewed PTCL cases diagnosed in our institution between 1990 and 2000 and selected eight cases for study based on the following criteria: small-cell morphology with abundant, clear cytoplasm and either marginal zone involvement by the neoplastic infiltrate in lymph node biopsies or lymphoepithelial lesions in extranodal bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 9 publications
0
34
0
2
Order By: Relevance
“…Uherova et al studied histologic specimens from eight patients that included six lymph node biopsies and four extranodal biopsies composed of uniform, small-to-intermediate-sized, lymphoid cells with round or slightly irregular nuclei and abundant pale or clear cytoplasm. 39 However, in all specimens, the neoplastic cells were positive for CD3 by immunohistochemistry. The six specimens in which gene rearrangement studies were performed showed monoclonal gene rearrangement of the T-cell receptor ␤ chain in the absence of immunoglobulin gene rearrangement.…”
Section: Differential Diagnosismentioning
confidence: 85%
“…Uherova et al studied histologic specimens from eight patients that included six lymph node biopsies and four extranodal biopsies composed of uniform, small-to-intermediate-sized, lymphoid cells with round or slightly irregular nuclei and abundant pale or clear cytoplasm. 39 However, in all specimens, the neoplastic cells were positive for CD3 by immunohistochemistry. The six specimens in which gene rearrangement studies were performed showed monoclonal gene rearrangement of the T-cell receptor ␤ chain in the absence of immunoglobulin gene rearrangement.…”
Section: Differential Diagnosismentioning
confidence: 85%
“…Our case shows that the same clone of T cell expressing a phenotype similar to that of normal follicular helper T cells may present with different patterns: AITL, a condition well known [1][2][3]6]; FTCL, a less frequent condition [7][8][9][10][11][13][14][15]; and PTCL-unspecified, large-cell predominant.…”
Section: Discussionmentioning
confidence: 98%
“…The report that human peripheral T-cell lymphoma (TZL) may mimic MZL is highly applicable to the dog. 49 A subtle difference in architecture exists between MZL where the proliferation is concentric and encircles the fading germinal centers, whereas in TZL, the proliferation is eccentric to the residual B-cell foci.…”
Section: Discussionmentioning
confidence: 99%
“…7a). 22,36,45,49 Cytologically, TZL is composed of homogeneous population of CD3 + small lymphocytes that have sharp, shallow nuclear indentations, inapparent nucleoli, and a moderate volume of pale cytoplasm (Fig. 7b).…”
Section: Diagnostic Criteriamentioning
confidence: 99%